Industry 4.0 and innovations for Mechanical Engineering (Research, Society and Development, 2023)
When discussing innovation, Industry 4.0 emerges as an advanced stage in the Industrial Revolution, with the potential to stimulate economic growth and progress. Due to this large-scale production, there was an increase in demand for mechanical engineers, this was due to the increasing complexity of production processes, machine maintenance and other factors. Therefore, the objective of this study was to investigate the innovations brought by industry 4.0 in the field. mechanical engineering, among these innovations the impact, challenges and benefits of industry 4.0 in this area in question were also addressed; manufacturing in the context of industry 4.0 principles and tools and technologies in the applicability of maintenance. In the results section, the topics outlined in the objective were addressed, along with more detailed exploration of other related spheres. To prepare this research, an integrative literature review study was carried out. Continuous competence in adapting the production system is essential for manufacturing success. Professionals prepared for Era 4.0 see a promising future. There is a demand for innovative and skilled individuals with technical knowledge, while the innovations of Revolution 4.0 challenge several areas, especially engineering. Mechanical engineering maintains a crucial role in industry, while artificial intelligence optimizes processes. The relevance of the human factor persists when AI is not enough. Mechanics will continue to be vital in Era 4.0, automating tasks and allowing approaches in other areas.